Le centenaire de Paul Hymans - Jaspar, Henri (S.l. : s.n., 1965)
Bibliotheek Camille Huysmans
Dedicator: Jaspar, Henri, dedicatee: Huysmans, Camille
Overdruk ui: La Revue des deux mondes, 1 juni 1965
Frans
Brochure
Keywords: Hymans, Paul